2003
DOI: 10.1074/jbc.m304654200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor-γ Represses GLUT4 Promoter Activity in Primary Adipocytes, and Rosiglitazone Alleviates This Effect

Abstract: The synthetic thiazolidinedione ligands of peroxisome proliferator-activated receptor-␥ (PPAR␥) improve insulin sensitivity in type II diabetes and induce GLUT4 mRNA expression in fat and muscle. However, the molecular mechanisms involved are still unclear. We studied the regulatory effects of PPAR␥ and its ligands on GLUT4 gene expression in primary rat adipocytes and CHO-K1 cells cotransfected with PPAR␥ and the GLUT4 promoter reporter. PPAR␥1 and PPAR␥2 repressed the activity of the GLUT4 promoter in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 35 publications
11
109
1
3
Order By: Relevance
“…It has earlier been demonstrated that the insulin sensitive GLUT4 (now known as solute carrier family 2 [facilitated glucose transporter], member 4 [SLC2A4]) promoter is repressed by PPARG in primary adipocytes [22]. Consequently, the low PPARG activity in the intra-abdominal fat cells is in line with the high levels of GLUT4 in intraabdominal as compared with subcutaneous adipocytes that were reported by us earlier [23].…”
Section: Discussionmentioning
confidence: 74%
“…It has earlier been demonstrated that the insulin sensitive GLUT4 (now known as solute carrier family 2 [facilitated glucose transporter], member 4 [SLC2A4]) promoter is repressed by PPARG in primary adipocytes [22]. Consequently, the low PPARG activity in the intra-abdominal fat cells is in line with the high levels of GLUT4 in intraabdominal as compared with subcutaneous adipocytes that were reported by us earlier [23].…”
Section: Discussionmentioning
confidence: 74%
“…However, a recent study has shown that the PPAR/retinoic X receptor heterodimer exerts an inhibitory effect on GLUT4 promoter activity, and that thiazolidinedione binding to the receptor alleviates this repression [37]. However, other mechanisms could also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…They showed how a PPAR-g ligand, rosiglitazone, ameliorates insulin resistance in NIDDM. Rosiglitazone increases GLUT4 mRNA level in the diabetic model, whereas 15-deoxy-D12,14-prostaglandin J2 (15 D-PGJ2) represses GLUT4 gene expression in myocytes and adipocytes (121). PPAR-g-mediated suppression occurs through the binding of the PPAR-g/RXR-a heterodimer to the PPRE in the GLUT4 promoter, and the repression is relieved by synthetic ligands through the ligand-binding domain.…”
Section: Free Fatty Acids (Ffa)mentioning
confidence: 99%
“…Its ligand regulates glucose homeostasis and lipid metabolism (120). Armoni et al (121) identified a PPAR-g response element (PPRE) in the 766/þ163 bp region of the GLUT4 promoter, suggesting that PPAR-g down-regulates GLUT4 gene transcription through direct binding to the PPRE. However, with regard to the regulation of GLUT4 gene expression, some conflicting results were obtained from the experiments using natural and synthetic ligands.…”
Section: Free Fatty Acids (Ffa)mentioning
confidence: 99%